CURRICULUM AND SPECIAL EDUCATION: A LITERATURE REVIEW - dos Santos, Luciana Araujo; Mesquita, Amélia Maria Araújo (Seven Editora, 2026)
This paper aims to reflect on the curriculum of Specialized Educational Assistance (AEE) in Multifunctional Resource Rooms (SRM), based on a literature review on curriculum and special education. It is grounded in the understanding of curriculum as a social and historical construction, shaped by power relations that guide the selection of knowledge (Young, 2014; Sacristán, 2000, 2013; Lopes & Macedo, 2011). The study adopts a qualitative approach, using bibliographic research as its methodological foundation. The analysis shows that both curriculum and Special Education are fields marked by disputes that directly impact the organization of AEE, especially regarding its complementary and supplementary dimensions (Bueno, 2016; Capellini, 2012, 2014; Mendes, 2010, 2018; Glat, 2011, 2018; Kassar, 2011, 2016). It concludes that AEE should not be reduced to technical or compensatory practices, but rather understood as a curricular service, articulated with the mainstream classroom curriculum, aiming at democratizing access to knowledge and promoting inclusive education.